Penerapan Video Pembelajaran Interaktif dalam Pembelajaran Daring untuk Meningkatkan Hasil Belajar Matematika Materi Aritmetika Sosial - Mirah Wahyuningrum (Journal of Instructional Development Research, 2023)
The purpose of this study was to improve the mathematics learning outcomes of social arithmetic materials through the application of interactive learning videos in online learning for class VII.C students of SMP Negeri 10 Bekasi City. The subjects of this study were students of class VII.C SMP Negeri 10 Bekasi City as many as 40 students. The research method used is Classroom Action Research. Methods of data collection using tests, observation sheets, interviews, and documentation. The results showed that the use of interactive learning videos in online learning activities for mathematics subjects was more effective and fun for students, not boring, because the display on interactive learning videos was audio-visual in nature. The results of evaluation tests that measure students' understanding of social arithmetic material, in the pre-cycle the class average score is 70.93 with 52.50% completeness, it increases in the first cycle with an average value of 78.38 with 72.50% completeness , and increased again in the second cycle with an average value of 82.08 with a completeness of 92.50%. The conclusion of this study through interactive learning videos in online learning can improve mathematics learning outcomes in social arithmetic material for class VII.C students of SMP Negeri 10 Bekasi City.